Sexo, Género y Poder: breve reflexión sobre algunos conceptos manejados en la Arqueología del Género - Hernando Gonzalo, Almudena (Complutum, 2007)
This text wants to discuss some concepts implied in Archaeology of Gender, such as sex, gender or power. These terms were never included in the positivist tradition of Archaeology, which projected a pretended neutral –but in reality patriarchal– order of the modern society to the past. Therefore, their use obliges to introduce studies and analysis coming from different disciplines. In the author opinion, only doing this, it will be possible to understand the complex and dynamic construction of human identity and of gender identity.